Science communication models in research downstreaming at Indonesian universities - Saputro, Eko Prasetyo Nugroho; Nurhaeni, Ismi Dwi Astuti; Rahmanto , Andre N.; Hastjarjo, Sri (Jurnal Cakrawala Pendidikan, 2026)
Indonesian universities are mandated to disseminate research and innovations to support national development; however,  a gap persists between knowledge production and its broader societal utilization. This study examines how science communication models operate within research downstreaming at Universitas Indonesia (UI), Universitas Gadjah Mada (UGM), and Institut Teknologi Bandung (ITB) using the deficit, contextual, lay expertise, public engagement, and hybrid models. A qualitative multiple-case study was conducted from September 2024 to January 2025 through in-depth interviews with 15 institutional informants and document analysis. Findings indicate that early downstreaming is largely dominated by deficit-oriented communication through journal outputs and institutional websites that prioritize academic validation and performance indicators, while later stages increasingly employ contextual, participation, and lay expertise models through cross-sector forums, policy interfaces, digital platforms, innovation events, and community service. Importantly, hybrid (multimodel) practices are present across both early and advanced stages, indicating that universities flexibly combine models to meet shifting objectives and stakeholder configurations from validation to adoption. The study concludes that downstreaming involves a communicative reconfiguration where adaptive multimodel strategies are essential to secure credibility, relevance, and uptake.